PENGARUH PERAN ORANG TUA DAN STUDY FROM HOME (SFH) TERHADAP HASIL BELAJAR SISWA SD 130 KEPULAUAN SELAYAR - Iskandar . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This study aims to determine (1) the effect of parental roles on student learning outcomes at SD 130 Selayar Islands (2) the effect of Study From Home (SFH) on student learning outcomes at SD 130 Selayar Islands (3) the influence of the role of parents and Study From Home ( SFH) simultaneously on Student Learning Outcomes of SD 130 Selayar Islands. This type of research is quantitative which is used to answer research problems related to data in the form of numbers and statistical programs. This research was conducted at SD 130 Selayar Islands. The population in this study were all students with the number of samples for class VI, namely 9 people. Data collection techniques using questionnaires and documentation. The data analysis technique used descriptive analysis and multiple linear regression analysis. The results showed that 1) there was an influence of the role of parents on the learning outcomes of SD 130 Selayar Islands students 2) there was an influence of Study From Home (SFH) on the learning outcomes of SD 130 Selayar Islands students 3) there was an influence of the role of parents and Study From Home (SFH) simultaneously on student learning outcomes of SD 130 Selayar Islands. Keywords: Parents, Study From Home (SFH), Student Learning Outcomes, Linear Regression